The formation of S0 galaxies with counter-rotating neutral and molecular hydrogen. Issue 2 (3rd May 2017) - Bassett, Robert; Bekki, Kenji; Cortese, Luca; Couch, Warrick
Abstract: The observation of counter-rotation in galaxies (i.e. gas that rotates in the opposite direction to the stellar component or two cospatial stellar populations with opposite rotation) is becoming more commonplace with modern integral field spectroscopic surveys. In this paper, we explore the emergence of counter-rotation (both stellar and gaseous) in S0 galaxies from smoothed-particle hydrodynamics simulations of 1/10 mass ratio minor mergers between a ∼10 10.8 M⊙ disc galaxy with a bulge-to-total ratio of 0.17 and a gas-rich companion (gas-to-stellar mass fraction of 5.0). These simulations include a self-consistent treatment of gas dynamics, star formation, the production/destruction of H2 and dust and the time evolution of the interstellar radiation field. We explore the effect of retrograde versus prograde obits, gas and bulge mass fractions of the primary galaxy, and orbital parameters of the companion. The key requirement for producing counter-rotation in stars or gas in a merger remnant is a retrograde primary, while the relative spin of the companion affects only the radial extent of the accreted gas. We also find that including a significant amount of gas in the primary can prevent the emergence of counter-rotating gas, although accreted stars retain counter-rotation. Bulge mass and orbit have a secondary effect, generally influencing the final distribution of accreted stars and gas within the framework outlined above. In addition to our primary focus of counter-rotating components in galaxies, we also make some predictions regarding the SFRs, H2 distributions, and dust in minor-merger remnants.